PENELITIAN EVALUASI PENYELENGGARAAN DIKLAT JARAK JAUH (DJJ) - Hayadin Hayadin (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2012)
AbstractThis study aims at determining the context, input, process and output of distance education and training organized by the Ministry of Religious Affairs since 2009. This study used the survey method at research sites covering Jakarta education and training center, Bandung education and training center, Surabaya education and training center, Semarang education and training center, Denpasar education and training center, Banjarmasin education and training center, Makassar education and training center, Padang education and training center, Palembang education and training center and Medan education and training center. The data collection was done by interviews, questionnaires, observations, and study of documents. The study concluded that distance education and training of technical personnel conducted since 2009 at 4 education and training centers and in 2010 at the entire education and training centers (12 education and training centers) have contributed to three things: a). Increasing the number of education and training participants, b). Providing ICT competencies to lecturers and staff of education and training centers to be on-line tutors and administrators of distance education and training, and c). Providing Virtual Learning Environment (VLE), hardware and software in the form of internet websites with contents that support the distance learning.AbstrakPenelitian ini bertujuan untuk mengetahui konteks, input, proses dan output penyelenggaraan diklat jarak jauh yang diselenggarakan oleh Kementerian Agama RI sejak tahun 2009. Penelitian ini menggunakan metode survei, pada lokasi penelitian yang meliputi balai diklat Jakarta, balai diklat Bandung, balai diklat Surabaya, balai diklat Semarang, balai diklat Denpasar, balai diklat Banjarmasin, balai diklat Makassar, balai diklat Padang, balai diklat Palembang dan balai diklat Medan. Pengumpulan data menggunakan teknik wawancara, angket, observasi, dan studi dokumen. Penelitian menyimpulkan bahwa penyelenggaraan diklat jarak jauh tenaga teknis dilaksanakan sejak tahun 2009 pada 4 balai diklat dan pada tahun 2010 pada seluruh balai diklat (12 BDK) telah memberikan kontribusi terhadap tiga hal, yaitu: a). Meningkatkan jumlah peserta diklat; b). Memberikan kompetensi TIK kepada widyaiswara dan staf balai diklat untuk menjadi tutor on-line dan administrator diklat-jarak jauh; dan c). Menyediakan Virtual Learning Environtment (VLE), hardware dan software dalam bentuk web-site internet dengan content yang mendukung pembelajaran jarak jauh.